2015
DOI: 10.1002/2015gb005106
|View full text |Cite
|
Sign up to set email alerts
|

Global oceanic emission of ammonia: Constraints from seawater and atmospheric observations

Abstract: Current global inventories of ammonia emissions identify the ocean as the largest natural source. This source depends on seawater pH, temperature, and the concentration of total seawater ammonia (NH x (sw)), which reflects a balance between remineralization of organic matter, uptake by plankton, and nitrification. Here we compare [NH x (sw)] from two global ocean biogeochemical models (BEC and COBALT) against extensive ocean observations. Simulated [NH x (sw)] are generally biased high. Improved simulation can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
135
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(151 citation statements)
references
References 127 publications
15
135
1
Order By: Relevance
“…The number of data points reported for each database are after gridding to 1 • × 1 • × 12 months × 33 depths (World Ocean Atlas 2009). The databases used are (1) NH + cific nitrification rate (d −1 , raw data n = 425, gridded data n = 296) as described in Yool et al (2007); (2) surface NH + 4 concentration distribution (µmol L −1 , raw data n = 33 079, gridded data n = 2343) that combines the dataset used in Paulot et al (2015) with data held by the British Oceanographic Data Centre (Martin Johnson, personal communication, 2015, http://www.bodc.ac.uk, last access: January 2014); (3) depth-resolved N 2 O concentration from the MEMENTO project (nmol L −1 , https://memento.geomar. de/; Bange et al, 2009; downloaded 4 June 2014, raw data n = 14 342, gridded data n = 8047); and (4) surface partial pressure of N 2 O (pN 2 O) also from MEMENTO (ppb, downloaded 16 September 2015, raw data n = 227 463, gridded data n = 6136).…”
Section: Observational Databases For Model Developmentmentioning
confidence: 99%
“…The number of data points reported for each database are after gridding to 1 • × 1 • × 12 months × 33 depths (World Ocean Atlas 2009). The databases used are (1) NH + cific nitrification rate (d −1 , raw data n = 425, gridded data n = 296) as described in Yool et al (2007); (2) surface NH + 4 concentration distribution (µmol L −1 , raw data n = 33 079, gridded data n = 2343) that combines the dataset used in Paulot et al (2015) with data held by the British Oceanographic Data Centre (Martin Johnson, personal communication, 2015, http://www.bodc.ac.uk, last access: January 2014); (3) depth-resolved N 2 O concentration from the MEMENTO project (nmol L −1 , https://memento.geomar. de/; Bange et al, 2009; downloaded 4 June 2014, raw data n = 14 342, gridded data n = 8047); and (4) surface partial pressure of N 2 O (pN 2 O) also from MEMENTO (ppb, downloaded 16 September 2015, raw data n = 227 463, gridded data n = 6136).…”
Section: Observational Databases For Model Developmentmentioning
confidence: 99%
“…Unlike largerscale studies of Arctic precipitation showing sulfur to be the main acidifying substance (Hole et al, 2009) (Table 5). At the coast, NO is comparable (17 mol ha −1 a −1 ), possibly suggesting an influence of ammonium sulfate aerosols (Fisher et al, 2011;Paulot et al, 2015). Local urban, marine or shipping emis-sions could also account for higher deposition fluxes of all these ions in coastal snowpack, especially given the proximity of the town and port at Sisimiut, but since NO Modelled wet deposition of nss-SO 2− 4 for western Greenland in a global analysis was found to be in the region of 0.2 kg ha −1 a −1 S (Vet et al, 2014), which falls in the middle of the spatial range suggested by our study (0.08-0.35 kg ha −1 a −1 ).…”
Section: Deposition Estimatesmentioning
confidence: 99%
“…With a share of around 70-80 %, the bulk of ammonia emissions is due to anthropogenic activity, namely the use of synthetic fertilizers and livestock manure management (Bouwman et al, 1997;Paulot et al, 2015). Major source regions of NH 3 are located in southeast China and northern India (Paulot et al, 2014;Van Damme et al, 2015).…”
Section: Introductionmentioning
confidence: 99%